Comparison of Creep Properties of Cast and Wrought Haynes 282 Superalloy - Young-Joo Kim; Jae-Hyeun Park; Yong-Sik Ahn (Advances in Materials Science and Engineering)
Ni-based superalloy Haynes 282 was developed as a gas turbine material for use in the ultra-supercritical (USC) stage of next-generation coal-fired power plants. Temperatures in the USC stage exceed 700°C during operation. Despite the important role of Haynes 282 in increasing the performance of high-pressure turbines, as a result of its high-temperature capability, there is little information on the microstructure, deformation mechanism, or mechanical properties of the cast condition of this alloy. In this study, we compared the creep properties of Haynes 282 cast alloy with those of its wrought alloy counterpart. The tensile test results of cast and wrought Haynes 282 alloys over the temperature range 25–800°C showed that the cast product exhibited significantly lower strength and ductility compared with the wrought product at all test temperatures. A creep test performed at 750°C showed only a slight difference in the rupture life of the two products. Based on the creep test results, the deformation mechanism is discussed.